Toward a Mechanistic Understanding of Marine Invertebrate Behavior at Elevated CO2 - Thomas, Jodi T.; Munday, Philip L.; Watson, Sue-Ann (Frontiers in Marine Science, 2020)
Elevated carbon dioxide (CO2) levels can alter ecologically important behaviours in a range of marine invertebrate taxa; however, a clear mechanistic understanding of these behavioural changes is lacking. The majority of mechanistic research on the behavioural effects of elevated CO2 has been done in fish, focusing on disrupted functioning of the GABAA receptor (a ligand-gated ion channel, LGIC). Yet, elevated CO2 could induce behavioural alterations through a range of mechanisms that disturb different components of the neurobiological pathway that produces behaviour, including disrupted sensation, altered behavioural choices and disturbed ligand-gated ion channel-mediated neurotransmission. Here, we review the potential mechanisms by which elevated CO2 may affect marine invertebrate behaviours. Marine invertebrate acid-base physiology and pharmacology is discussed in relation to altered GABAA receptor functioning. Alternative mechanisms for behavioural change at elevated CO2 are considered and important topics for future research have been identified. A mechanistic understanding will be important to determine why there is variability in elevated CO2-induced behavioural alterations across marine invertebrate taxa, why some, but not other, behaviours are affected within a species and to identify which marine invertebrates will be most vulnerable to rising CO2 levels.